(untitled) (Global Journal of Management and Business Research, 2012)
This research was triggered by enthusiasm to conduct a comparative models experiment of indicators of Millennium Development Goals (MDGs) interaction with economic growth. To achieve the objectives of this research, three sets of econometric model were developed and thoroughly subjected to statistical analysis to determine MDGs models efficiency. The methodology employed is experimental approach to MDGs#x2019; indicators in the economy. The research revealed that, the second model is the best, more robust and contributes more in explaining the relationship between MDGs indicators and the economic growth. The third model was rated poor, while the first model was rated moderate in explaining MDGs indicators influence in the economy. The paper concludes that, this short run dynamic analysis can be extended to a long run analysis. It further provides policy makers in developing countries with unique analytical relationship between real growth rate of the economy and MDGs i ndelling.